Detection and amplification of capacitance- and charge-based signals using printed electrolyte gated transistors with floating gates. (1st November 2019) - Thomas, Mathew S; Dorfman, Kevin D; Frisbie, C Daniel
Abstract: The electrolyte gated transistor with a floating gate (FGT) is a promising sensing platform for both chemical and biodetection applications due to its fast, label-free response, low voltage operation, and simple fabrication by printing and conventional lithography. We present here a unified framework for understanding how FGTs measure changes in interfacial capacitance and surface charge, using self-assembled monolayers (SAMs) on the FGT detection area as model systems. The capacitance measurements take advantage of alkyl thiol SAMs with different chain lengths, while the charge experiments deprotonate 11-mercaptoundecanoic acid by changing solution pH. The effects of capacitance and surface charge are identified readily by analysis of the changes in the quasi-static current–voltage ( I D – V G ) characteristics of a stand-alone FGT in response to changes in the surface properties; changes in capacitance produce changes in slope, whereas changes in surface charge cause horizontal shifts in the transfer curves. For sensing applications, it is preferable to integrate the FGT into a resistor-loaded inverter to take advantage of the amplified voltage output relative to a stand-alone FGT. For inverters, changes in capacitance lead to changes in inverter gain, whereas changes in surface charge produce horizontal shifts in the inverter curves. A capacitance sensitivity of 70 mV/( μ F/cm 2 ) and a charge sensitivity of 40 mV/( μ C/cm 2 ) are obtained from the inverter output voltages. The ability to sense both capacitance and charge, and to distinguish between them, makes FGTs attractive for the detection of a wide variety of targets in chemical and biological sensing applications.